SPE Asia Pacific Oil and Gas Conference and Exhibition 1999
DOI: 10.2118/54351-ms
|View full text |Cite
|
Sign up to set email alerts
|

Application of Horizontal Well in Heterogeneity Gas Condensate Reservoir

Abstract: As a result of a low pressure around wellbore, a liquid condensate saturation ring radially propagates the well reducing the relative permeability to gas. This phenomenon can occur even if the average reservoir pressure remains above the dew point pressure. Unless the pressure gradient stabilises around the well, the condensate ring continues to grow and the gas-oil ratio varies accordingly. This paper presents application of horizontal well in heterogeneity gas condensate reservoir. Horizont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…• re-perforating the wellbore, and solvent injection (Al-Anazi et al 2005;Liangui et al 2000;Alzate et al 2006) • dry gas injection (condensate re-vaporization) (Smith and Yarborough 1968;Shi et al 2001) • water injection, nitrogen injection to drive condensate back (Siregar et al 1992) • increasing reservoir contact using horizontal well (Muladi and Pinczewski 1999) • hydraulic fracturing, and near wellbore wettability alteration are additional examples to mention Apart from the wettability alteration method, other methods are not permanent solutions and the condensate bank will re-form (Li and Firoozabadi 2000a). The latter authors (2000b) studied the gas condensate system using a phenomenological network model and investigated the effects of interfacial tension, gravity, flow rate, contact angle hysteresis and network size on the critical condensate saturation.…”
Section: Introductionmentioning
confidence: 99%
“…• re-perforating the wellbore, and solvent injection (Al-Anazi et al 2005;Liangui et al 2000;Alzate et al 2006) • dry gas injection (condensate re-vaporization) (Smith and Yarborough 1968;Shi et al 2001) • water injection, nitrogen injection to drive condensate back (Siregar et al 1992) • increasing reservoir contact using horizontal well (Muladi and Pinczewski 1999) • hydraulic fracturing, and near wellbore wettability alteration are additional examples to mention Apart from the wettability alteration method, other methods are not permanent solutions and the condensate bank will re-form (Li and Firoozabadi 2000a). The latter authors (2000b) studied the gas condensate system using a phenomenological network model and investigated the effects of interfacial tension, gravity, flow rate, contact angle hysteresis and network size on the critical condensate saturation.…”
Section: Introductionmentioning
confidence: 99%
“…According to this method, many scholars have studied the productivity of vertical wells in condensate gas reservoirs [6,8,22]. Some scholars have further established the four-region model [23][24][25][26][27], which takes into account the capillary effect and is the most comprehensive method; however, it increases the difficulty of modeling.…”
Section: Afidick Et Al Conducted a Constant Component Expansion (Cce)...mentioning
confidence: 99%
“…Kumar et al (2006a, b) found that the relative permeability to gas was improved and the residual oil saturation was reduced after treating the core samples with wettability-alteration chemicals. Wettability-alteration chemicals can reduce the high velocity (turbulent) coefficient as well as enhance the relative permeability to gas (Noh and Firoozabadi 2006). Also, wettability-alteration chemicals were found to be effective in modifying the wettability of rock surfaces in propped fractures, hence increasing the gas-flow rate through improving the fracture conductivity (Bang 2007;Bang et al 2008).…”
Section: Use Of Fluorosurfactants and -Polymers For Wettability Altermentioning
confidence: 99%